2018
DOI: 10.2460/javma.253.8.1038
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of vertebral left atrial size as determined from thoracic radiographs for assessment of left atrial size in dogs with myxomatous mitral valve disease

Abstract: OBJECTIVE To describe vertebral left atrial size (VLAS), a quantitative method to estimate left atrial (LA) size radiographically, and to determine its diagnostic value for prediction of echocardiographic LA enlargement in dogs with myxomatous mitral valve disease (MMVD) of varying severity. DESIGN Prospective observational study. ANIMALS 103 client-owned dogs with a left-sided systolic murmur. PROCEDURES For each dog, 3-view thoracic radiographs were obtained within 24 hours of an echocardiographic examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
143
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(185 citation statements)
references
References 20 publications
19
143
7
2
Order By: Relevance
“…(Class I, LOE: expert opinion) A newer index of radiographic left atrial enlargement, the VLAS, provides a quantitative method of estimating left atrial size. Measured on either the right or left lateral radiograph by drawing a line from the center of the most ventral aspect of the carina to the most caudal aspect of the LA where it intersects with the dorsal border of the caudal vena cava, that line then is transposed to the cranial edge of the 4th thoracic vertebral body . Studies are ongoing to determine a VLAS value that accurately predicts B2 remodeling, but in the absence of echocardiography, VLAS values of ≥3 likely identify Stage B2 MMVD.…”
Section: Guidelines For Diagnosis and Treatment Of Mmvdmentioning
confidence: 99%
“…(Class I, LOE: expert opinion) A newer index of radiographic left atrial enlargement, the VLAS, provides a quantitative method of estimating left atrial size. Measured on either the right or left lateral radiograph by drawing a line from the center of the most ventral aspect of the carina to the most caudal aspect of the LA where it intersects with the dorsal border of the caudal vena cava, that line then is transposed to the cranial edge of the 4th thoracic vertebral body . Studies are ongoing to determine a VLAS value that accurately predicts B2 remodeling, but in the absence of echocardiography, VLAS values of ≥3 likely identify Stage B2 MMVD.…”
Section: Guidelines For Diagnosis and Treatment Of Mmvdmentioning
confidence: 99%
“…Differences in VHS according to the canine breed have also been described 4‐11 . However, there are few studies in veterinary medicine aimed at standardizing the radiographic left atrial (LA) size 12‐15 …”
Section: Introductionmentioning
confidence: 99%
“…A newer index of radiographic LA size, the vertebral left atrial size (VLAS), was recently included in the American College of Veterinary Internal Medicine consensus guidelines for the diagnosis and treatment of myxomatous mitral valve disease 17 . One study proposed a cutoff of VLAS ≥ 2.3 vertebrae as a radiographic indicator of LA enlargement in dogs, but only 15 normal dogs were included in the study 13 . For the definition of a reference range in the canine population, a larger sample is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The vertebral left atrial size (VLAS) was measured by drawing the first line from the center of the most ventral aspect of the carina, the bifurcation of the left and right mainstem bronchi, to the most caudal aspect of the LA where it intersected with the dorsal border of the caudal vena cava. The line length was compared with the vertebral scale from the beginning at the cranial edge of the fourth thoracic vertebra on the lateral view 10 . For the qualitative assessment, LA enlargement was considered to be present when there was an elevation of the carina and dorsal bulging of the LA with loss of the gentle curvature of caudal margin of the cardiac silhouette in the lateral view.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the clock face analogy, when the LA is enlarged, a focal bulge of the left auricle can be found at the 2‐3 o'clock position. A recent study suggested that the vertebral left atrial size (VLAS) for quantifying the LA enlargement and VLAS has a moderate positive correction with the echocardiographic measurement of LA/Ao in both the long and short axes 10 . VLAS < 2.1 vertebrae has been suggested to be normal.…”
Section: Introductionmentioning
confidence: 99%